Quality of Life Analysis of Mental Disorder Patients Based on Knowledge Level and Medication Adherence - Alfianna, Wiwin; Sabrina, Nina; Rahmah, Nurlaily; Muliani, Rima (Indonesian Journal of Clinical Pharmacy, 2025)
Evaluating the quality of life (QoL) is essential in assessing therapeutic outcomes for individuals with mental health disorders. Medication adherence plays a pivotal role in treatment success but is frequently suboptimal due to insufficient patient knowledge regarding their illness and prescribed therapies, which can lead to misunderstandings and non-compliance. This research investigates the association between patients’ knowledge levels, adherence to medication regimens, and their quality of life within a population diagnosed with mental disorders. Employing a cross-sectional design, data were collected from 200 patients using standardized instruments, including a knowledge assessment questionnaire, the Morisky Medication Adherence Scale-8 (MMAS-8), and the WHO Quality of Life-BREF (WHOQOL-BREF). Statistical analyses, conducted via SPSS version 25.0, utilized Pearson’s correlation and multiple correlation tests to explore relationships among the variables. Findings indicated that 58% of participants possessed adequate knowledge about their condition and treatment, while 52% demonstrated low adherence to medication. Additionally, 61.5% reported a good quality of life. Significant positive correlations were observed between quality of life and both knowledge and medication adherence (P = 0.000). However, no significant direct relationship was found between knowledge and adherence levels. The study underscores that medication adherence is significantly linked to enhanced quality of life in patients with mental disorders. Although knowledge alone does not directly predict adherence, it, in conjunction with adherence, contributes to improved quality of life outcomes. These results emphasize the need for integrated strategies focusing on patient education and adherence promotion to optimize therapeutic benefits.